Interaction among Stakeholders in a School Setting - Geryl Cataraja (East Asian Journal of Multidisciplinary Research, 2022)
The study gives a new outlook and an insight in the performance of their school task which the teachers are expected to improve both the academic and the physical aspects of the child’s education. It is hoped that the results of this study can lead them to discover these needs and suggest ways with which these needs could be met without waiting for government aid to come. Theory Gathering-Inductive Method was employed by the researcher using an in-depth interview technique. The technique was used to gather valid and factual data from which to draw conclusions. Interviews with the Barangay officials were undertaken to verify the answers to the instrument.